1992
DOI: 10.1111/j.1365-313x.1992.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

The methylation patterns of chromosomal integration regions influence gene activity of transferred DNA in Petunia hybrida

Abstract: The regions of integration of a transferred DNA-fragment from three transgenic Petunia hybrida plants were analysed for their influence on the expression of the foreign DNA. Each of the three transformants, lines 16, 17 and 24, contained a fragment of a plasmid on which two genes were located, an npt-11 gene which renders the plants resistant to kanamycin and the A1 gene from Zea mays, a visible marker gene that leads to the production of a brick red anthocyanin pigment in the flowers. Inactivation of both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Previous studies have shown that certain regions exist in the plant genome where integration of transgenes does not result in expression of the ®nal protein product. Such regions include the heterochromatic areas located near the centromere of the chromosomes (ProÈ ls and Meyer 1992;Ye and Signer 1996). Simon and Knowles (1993) reported that integration of transgenes in telomeric regions, which are transcriptionally active areas in the plant genome, can also lead to gene silencing.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that certain regions exist in the plant genome where integration of transgenes does not result in expression of the ®nal protein product. Such regions include the heterochromatic areas located near the centromere of the chromosomes (ProÈ ls and Meyer 1992;Ye and Signer 1996). Simon and Knowles (1993) reported that integration of transgenes in telomeric regions, which are transcriptionally active areas in the plant genome, can also lead to gene silencing.…”
Section: Discussionmentioning
confidence: 98%
“…The literature shows that, even in single-copy T-DNA plants, many factors are responsible for the induction of low transgene expression. Beside the T-DNA integration position itself, linkage to repetitive sequences [44], the presence of neighboring highly methylated sequences [45], and the absence of MAR sequences near the integration site [26] are implicated as causative factors for the induction of low transgene expression. Additionally, an abrupt change in AT content [19] and the presence of vector backbone sequences [46] may reduce transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the true transformants a differential GUS expression was observed, as a strong expression was seen in some seedlings while a weak expression was observed in others. This could be due to different copy numbers of the transgene in the individual plants (Hobbs et al 1993;Tjokrokusumo et al 2000) or to methylation in the chromosomal integration regions (Prols and Meyer 1992).…”
Section: Selection Of Transformed Plants Through Gus Gene Expressionmentioning
confidence: 99%